The provenance of émigrés: the validity of measuring knowledge of places. Issue 6 (3rd July 2017) - van Veldhuizen, Tanja S.; Horselenberg, Robert; Stel, Mariëlle; Landström, Sara; Granhag, Pär Anders; van Koppen, Peter J.
ABSTRACT: Establishing the origin of those seeking asylum is essential but difficult as asylum seekers often cannot corroborate their origin claim with documents. The aim of the present study was to assess whether asking knowledge questions, sketch questions and impossible questions are valid methods to determine the veracity of an origin claim. Participants ( N = 105) from Tilburg (truth-tellers), Maastricht (partial liars) and Gothenburg (full liars) were asked to convince an interviewer that they originated from Tilburg. Half of them prepared and half of them did not prepare themselves for the interview. They were asked 10 knowledge questions typically asked to assess the credibility of origin claims, 4 impossible questions and 1 sketch question. Participants from Tilburg answered more questions correctly than participants from Maastricht and Gothenburg. Performance also improved with preparation. Even though the results did provide some support for the validity of assessing claims about origin by asking knowledge questions, the differences between the groups were modest, and it was impossible to correctly identify all truth-tellers and liars. Changing the output modality from verbal answering to sketching contributed to the credibility assessment of origin claims, whereas impossible questions were not discriminatory.